Enhancing the HDI (Human Development Index) Through the Implementation of An RO (Reverse Osmosis) Based Clean Water Supply System for the Community of Asemberit Hamlet, Sampang Regency, Madura (TEKAD : Teknik Mengabdi, 2025)
The demand for clean water continues to increase along with population growth, while its availability becomes increasingly limited. Clean water is essential for health, household activities, agriculture, and environmental sustainability. The criteria for potable water include a neutral pH, absence of excessive chemical substances, and no E. coli contamination. In coastal areas such as Sampang Regency, Madura, groundwater quality is generally low due to high salinity, alkalinity, and lime content, making it unsuitable for consumption. To address this issue, a clean water supply system based on Reverse Osmosis (RO) technology was developed to reduce odor, turbidity, and organic compounds. This program aims to produce potable water while improving public health, soil fertility, and community productivity. In addition to benefiting local communities and regional governments, this activity also serves as a medium for community service and research for the academic community of Universitas Brawijaya and supports the “1000 Villages” Community Service Program (KKN) in East Java.